Composite positive pole piece as well as preparation method and application thereof
By using a composite active material layer composed of small-particle lithium iron phosphate in the positive electrode sheet of a lithium-ion battery, the problems of low surface density, poor conductivity and low porosity of the positive electrode in the prior art are solved, and the battery rate performance and cycling performance are improved, while the production cost is controlled.
Patent Information
- Application Number
- CN202411926280.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The positive electrode of the existing lithium-ion battery has low surface density, poor conductivity, low internal porosity, difficult electrolyte infiltration, and high production cost.
The composite positive electrode sheet structure is adopted, which includes a current collector and an active material layer symmetrically arranged on both sides of the current collector. The active material layer is composed of small-particle lithium iron phosphate. The D50 of the first lithium iron phosphate is ≤12μm, and the D50 of the second lithium iron phosphate is ≤5μm. Through the use of small-particle lithium iron phosphate, lithium ions can quickly diffuse into the electrolyte during charging, reducing diffusion polarization and improving the rate performance of the battery.
It improves the rate performance and cycle performance of the battery, reduces the internal polarization of the battery, meets the needs of high energy density and high rateability, and controls production costs.
Smart Images

Figure CN119742310A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a composite positive electrode plate and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in the new energy industry due to their high specific energy density, wide temperature range, and long cycle life. The recent rapid development of new energy electric vehicles has placed higher demands on power batteries (high energy density, high rate capability, stable and safe operation, and long cycle life). The energy density of a battery is primarily limited by the amount of active material in the positive electrode and the thickness of the composite electrode. Existing technologies typically utilize double-layer coating, lithium supplementation, and structural design to optimize battery energy density.
[0003] Double-layer coating of the positive electrode increases the battery's energy density by increasing the areal density of the positive electrode and the amount of active material. However, as the areal density and thickness of the electrode increase, this negatively impacts the electrode's porosity and wettability, leading to increased transmission paths for electrons and lithium ions and increased internal polarization. After multiple cycles, lithium ions tend to accumulate on the electrode surface and become depleted near the current collector, resulting in a decrease in battery capacity and poor rate and cycle performance. The prior art discloses a positive electrode sheet, a preparation method thereof, and a battery, which improves the initial coulombic efficiency and energy density of the battery by adding a lithium supplement to the active material layer. Secondly, the lithium supplement will disperse the gas during the formation process, thereby increasing the porosity of the bottom layer. However, the lithium supplement needs to be formed at a high voltage, and severe gas production causes the internal pressure and temperature of the battery to increase, thereby affecting the negative electrode material. Secondly, adding the lithium supplement increases the cost of the battery; the prior art also discloses a positive electrode sheet and a preparation method for a battery including the positive electrode sheet, which improves the energy density of the battery by designing upper and lower layers of active material particles, but this method has low porosity at high surface density, which hinders the diffusion rate of lithium ions in the electrode, resulting in a decrease in discharge capacity; therefore, it is necessary and important to optimize the design of a double-layer coated high-load electrode structure. Summary of the Invention
[0004] The present application provides a composite positive electrode sheet and its preparation method and application, aiming to solve the problems of low surface density, poor conductivity, low internal porosity, difficult electrolyte infiltration and high production cost of the positive electrode sheet in the prior art.
[0005] In a first aspect, the present application provides a composite positive electrode sheet, comprising a current collector and active material layers symmetrically arranged on both sides of the current collector;
[0006] The active material layer includes a first active material layer and a second active material layer; the current collector, the first active material layer and the second active material layer are sequentially overlapped;
[0007] The first active material layer includes a first lithium iron phosphate, a first conductive agent and a first binder;
[0008] The second active material layer includes a second lithium iron phosphate, a second conductive agent and a second binder;
[0009] The D50 of the first lithium iron phosphate is ≤12 μm, the primary particle size is 50-300 nm, and the secondary particles are formed by connecting multiple primary particles; the D50 of the second lithium iron phosphate is ≤5 μm.
[0010] The composite positive electrode plate described in this application uses small-particle lithium iron phosphate as the material of the outer active material layer. During the charging process, the lithium ions in the small-particle lithium iron phosphate can quickly diffuse into the electrolyte, thereby reducing the polarization of the diffusion and improving the battery's rate performance.
[0011] According to some embodiments of the composite positive electrode sheet described in the present application, D50 of the first lithium iron phosphate satisfies 6μm≤D50≤12μm, and D50 of the second lithium iron phosphate satisfies 0.8≤D50≤2.0μm.
[0012] According to some embodiments of the composite positive electrode sheet of the present application, the surface density of the first active material layer is 50-300 g / m 2 The surface density of the second active material layer is 50-300 g / m 2 .
[0013] According to some embodiments of the composite positive electrode sheet described in the present application, the ratio of the thickness of the first active material layer to the thickness of the second active material layer is (3-5):(5-7).
[0014] According to some embodiments of the composite positive electrode sheet described in the present application, the current collector includes aluminum foil and / or carbon-coated aluminum foil.
[0015] According to some embodiments of the composite positive electrode sheet described in the present application, the first conductive agent and the second conductive agent each independently include conductive carbon black.
[0016] According to some embodiments of the composite positive electrode sheet described herein, the first binder and the second binder each independently include polyvinylidene fluoride.
[0017] According to some embodiments of the composite positive electrode sheet described in the present application, the mass ratio of the first lithium iron phosphate to the first conductive agent is (96-97): (1-1.5).
[0018] According to some embodiments of the composite positive electrode sheet described in the present application, the mass ratio of the first lithium iron phosphate to the first binder is (96-98):2.
[0019] According to some embodiments of the composite positive electrode sheet described in the present application, the mass ratio of the second lithium iron phosphate to the second conductive agent is (96-98): (1-1.5).
[0020] According to some embodiments of the composite positive electrode sheet described in the present application, the mass ratio of the second lithium iron phosphate to the second binder is (96-98):2.
[0021] The second aspect of the present application provides a method for preparing the composite positive electrode sheet according to the first aspect of the present application, comprising the following steps:
[0022] (1) Preparation of the first layer of active material slurry:
[0023] Mixing a first lithium iron phosphate, a first conductive agent, a first binder, and a first solvent to obtain a first active material slurry;
[0024] (2) Preparation of the second layer of active material slurry:
[0025] mixing a second lithium iron phosphate, a second conductive agent, a second binder, and a second solvent to obtain a second active material slurry;
[0026] (3) The first active material slurry and the second active material slurry are simultaneously coated on the current collector and dried to obtain the composite positive electrode sheet.
[0027] According to some embodiments of the method for preparing a composite positive electrode sheet described in the present application, the first solvent and the second solvent each independently include nitrogen-methylpyrrolidone.
[0028] According to some embodiments of the method for preparing a composite positive electrode sheet described in the present application, the solid content of the first active material slurry is 60%-64%.
[0029] According to some embodiments of the composite positive electrode sheet preparation method described in the present application, the fineness of the first active material slurry is ≤20um.
[0030] According to some embodiments of the composite positive electrode sheet preparation method described in the present application, the viscosity of the first active material slurry is 5000-6000 mPa.s.
[0031] According to some embodiments of the composite positive electrode sheet preparation method described in the present application, the solid content of the second active material slurry is 60%-64%.
[0032] According to some embodiments of the composite positive electrode sheet preparation method described in the present application, the fineness of the second active material slurry is ≤20 um.
[0033] According to some embodiments of the composite positive electrode sheet preparation method described in the present application, the viscosity of the second active material slurry is 5000-6000 mPa.s.
[0034] According to some embodiments of the method for preparing the composite positive electrode sheet described in the present application, the drying temperature is 80-110° C., and the drying time is 20-45 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope (SEM) test image of lithium iron phosphate in the first active material layer in Example 1;
[0036] Figure 2 This is a scanning electron microscope (SEM) test image of lithium iron phosphate in the second active material layer in Example 1. DETAILED DESCRIPTION
[0037] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0038] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.
[0039] The embodiment of the present application provides a composite positive electrode sheet, comprising a current collector and active material layers symmetrically arranged on two sides of the current collector;
[0040] The active material layer includes a first active material layer and a second active material layer; the current collector, the first active material layer and the second active material layer are sequentially overlapped;
[0041] The first active material layer includes a first lithium iron phosphate, a first conductive agent and a first binder;
[0042] The second active material layer includes a second lithium iron phosphate, a second conductive agent and a second binder;
[0043] The D50 of the first lithium iron phosphate is less than or equal to 12 μm, and the D50 of the second lithium iron phosphate is less than or equal to 5 μm. The first lithium iron phosphate with a D50 less than or equal to 12 μm is a secondary spherical agglomerate formed by agglomeration of fine primary particles (from Figure 1 As can be seen in the figure, the lithium iron phosphate spheres themselves have many gaps, that is, porous lithium iron phosphate. This porous lithium iron phosphate has better wettability, can fully penetrate to ensure the effective transfer of positive electrode activity and electrolyte, and has better dynamics than other large-particle lithium iron phosphate.
[0044] Small-particle lithium iron phosphate is used as the material of the outer active material layer. During the charging process, the lithium ions in the small-particle lithium iron phosphate can quickly diffuse into the electrolyte, thereby reducing the polarization of the diffusion and improving the battery's rate performance.
[0045] In some embodiments of the present application, D50 of the first lithium iron phosphate satisfies 6 μm≤D50≤12 μm, and D50 of the second lithium iron phosphate satisfies 0.8 μm≤D50≤2.0 μm.
[0046] In some embodiments of the present application, the surface density of the first active material layer is 50-300 g / m 2 The surface density of the second active material layer is 50-300 g / m 2 ; When the thickness of the electrode is controlled to be constant, the energy density of the battery cell can be guaranteed within this range while reducing the polarization of the battery cell and improving the cycle performance of the battery cell; exceeding the range will have certain adverse effects, such as the total surface density (first active layer density + second active layer density) is too high, which will increase the amount of active material accordingly, resulting in the porosity and wettability of the electrode sheet to deteriorate, thereby affecting the capacity of the positive electrode material; when the total surface density is too low, the energy density of the battery cell will be low and cannot meet the usage requirements.
[0047] In some embodiments of the present application, the ratio of the thickness of the first active material layer to the thickness of the second active material layer is (3-5):(5-7). Increasing the content of lithium iron phosphate with larger particles facilitates rapid electrolyte infiltration and lithium ion diffusion, significantly improving the rate capability and cycle performance of the battery. However, excessive content of lithium iron phosphate with larger particles can reduce the volumetric energy density of a single battery.
[0048] In some embodiments of the present application, the current collector includes aluminum foil and / or carbon-coated aluminum foil.
[0049] In some embodiments of the present application, the first conductive agent and the second conductive agent each independently include conductive carbon black.
[0050] In some embodiments of the present application, the first binder and the second binder each independently include polyvinylidene fluoride.
[0051] In some embodiments of the present application, the mass ratio of the first lithium iron phosphate and the first conductive agent is (96-97): (1-1.5). Controlling the mass ratio of the first lithium iron phosphate and the first conductive agent within this range can ensure the conductivity of the positive electrode plate and the design requirements of the battery cell capacity; if it is higher than this range, the conductive agent content is relatively small, the internal resistance of the battery cell increases, and the polarization is large, affecting the capacity; if it is lower than this range, the positive electrode active material is less and the battery cell capacity is relatively small.
[0052] In some embodiments of the present application, the mass ratio of the first lithium iron phosphate and the first binder is (96-98):2. The mass ratio of the first lithium iron phosphate and the first binder is controlled within this range to ensure the peel strength of the electrode (avoid powder loss) while meeting the capacity of the positive electrode activity; if it is higher than this range, the peel strength of the electrode is insufficient, the electrode is prone to powder loss, resulting in poor battery cell cycle; if it is lower than this range, the binder content is too high, the active main material is relatively reduced, and the capacity is relatively low. Secondly, the conductivity of the binder is poor, and too high a binder content will affect the polarization of the battery cell.
[0053] In some embodiments of the present application, the mass ratio of the second lithium iron phosphate to the second conductive agent is (96-98): (1-1.5).
[0054] In some embodiments of the present application, the mass ratio of the second lithium iron phosphate to the second binder is (96-98):2.
[0055] The present application also provides a method for preparing the composite positive electrode sheet according to the first aspect of the present application, comprising the following steps:
[0056] (1) Preparation of the first layer of active material slurry:
[0057] Mixing a first lithium iron phosphate, a first conductive agent, a first binder, and a first solvent to obtain a first active material slurry;
[0058] (2) Preparation of the second layer of active material slurry:
[0059] mixing a second lithium iron phosphate, a second conductive agent, a second binder, and a second solvent to obtain a second active material slurry;
[0060] (3) The first active material slurry and the second active material slurry are simultaneously coated on the current collector and dried to obtain the composite positive electrode sheet.
[0061] The composite positive electrode sheet described in the present application satisfies the requirement of low polarization at high surface density, ensuring the energy density of the battery cell while also ensuring rate performance.
[0062] In some embodiments of the present application, the first solvent and the second solvent each independently include nitrogen methyl pyrrolidone.
[0063] In some embodiments of the present application, the solid content of the first active material slurry is 60%-64%. The solid content of the slurry directly affects the production cost. Too low a solid content will increase the amount of raw materials used, thereby increasing the production cost; while too high a solid content will lead to an unstable electrode structure and affect battery performance; this range ensures that the surface density is stable during the coating process; for example, 60%, 62%, 63%, 64%, etc.
[0064] In some embodiments of the present application, the fineness of the first active material slurry is ≤20um; for example, 20um, 18um, 15um, 12um, 10um, etc.
[0065] In some embodiments of the present application, the viscosity of the first active material slurry is 5000-6000 mPa.s. The viscosity in this range ensures the uniformity and stability of the coating. Too high a slurry viscosity has poor leveling, resulting in uneven coating. Low-viscosity slurry has good leveling but is difficult to dry, and is prone to problems such as coating cracking and slurry particle agglomeration, for example, 5000 mPa.s, 5500 mPa.s, 5700 mPa.s, 6000 mPa.s, etc.
[0066] In some embodiments of the present application, the solid content of the second active material slurry is 60%-64%, for example, 60%, 62%, 63%, 64%, etc.
[0067] In some embodiments of the present application, the fineness of the second active material slurry is ≤20um; for example, 20um, 18um, 15um, 12um, 10um, etc.
[0068] In some embodiments of the present application, the viscosity of the second active material slurry is 5000-6000 mPa.s, for example, 5000 mPa.s, 5500 mPa.s, 5700 mPa.s, 6000 mPa.s, etc.
[0069] In some embodiments of the present application, the drying temperature is 80-110°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, etc., and the drying time is 20-45min, for example, 20min, 25min, 30min, 35min, 40min, 45min, etc.
[0070] The technical solution of this application is further explained below with reference to specific implementation cases and drawings.
[0071] Example 1
[0072] A method for preparing a composite positive electrode sheet comprises the following steps:
[0073] (1) A first lithium iron phosphate having a D50 of 9 μm, a first conductive agent (SP conductive carbon black), and a first binder (PVDF) were mixed in a mass ratio of 96.5:1.5:2, and uniformly dispersed and adjusted in a stirring tank by adding a solvent NMP to obtain a first layer active material slurry having a viscosity of 6000 mPa.s, a solid content of 62%, and a particle fineness of ≤20 μm. The SEM image of the first lithium iron phosphate in the first layer active material slurry is shown in FIG. Figure 1 shown.
[0074] (2) The second lithium iron phosphate with a D50 of 1.5 μm, the second conductive agent (SP conductive carbon black), and the second binder (PVDF) were mixed in a mass ratio of 96.5:1.5:2, and the mixture was uniformly dispersed and the viscosity was adjusted in a stirring tank by adding a solvent NMP to obtain a second layer active material slurry with a viscosity of 6000 mPa.s, a solid content of 62%, and a particle fineness of ≤20 μm; the SEM image of the second lithium iron phosphate in the second layer active material slurry is shown in FIG. Figure 2 shown.
[0075] (3) The first active material slurry and the second active material slurry were coated on the carbon-coated aluminum foil of the current collector by extrusion (double independent coating chamber), and dried at 90 ° C for 20 minutes, and then coated on the other side of the current collector to obtain a thickness of 37.5 μm and a surface density of 75 / m 2 The first active material layer has a thickness of 87.5 μm and an area density of 175 g / m 2 The composite positive electrode sheet has a second active material layer.
[0076] Example 2
[0077] The only difference between Example 2 and Example 1 is that the thickness of the first active material layer and the thickness of the second active material layer are different from those in Example 1.
[0078] In Example 2, the surface density of the first active material layer is 125 g / m 2 The surface density of the second active material layer is 125 g / m 2 , the ratio of the thickness of the first active material layer to the thickness of the second active material layer is 5:5.
[0079] Comparative Example 1
[0080] The only difference between Comparative Example 1 and Example 1 is that in the composite positive electrode sheet of Comparative Example 1, the D50 of the first lithium iron phosphate is 15 μm.
[0081] Comparative Example 2
[0082] The only difference between Comparative Example 2 and Example 1 is that, in the composite positive electrode sheet described in Comparative Example 2, D50 of the first lithium iron phosphate is ≤5 μm.
[0083] Comparative Example 3
[0084] The only difference between Comparative Example 3 and Example 1 is that, in the composite positive electrode sheet described in Comparative Example 36, D50 of the first lithium iron phosphate is ≤5 μm, and D50 of the second lithium iron phosphate is ≤12 μm.
[0085] Comparative Example 4
[0086] The only difference between Comparative Example 4 and Example 1 is that, in the composite positive electrode sheet described in Comparative Example 4, the ratio of the thickness of the first active material layer to the thickness of the second active material layer is 7:3.
[0087] Comparative Example 5
[0088] The only difference between Comparative Example 5 and Example 1 is that the thickness of the first active material layer and the thickness of the second active material layer in the composite positive electrode sheet described in Comparative Example 5 are different from the thickness of the first active material layer and the thickness of the second active material layer in Example 1.
[0089] In Comparative Example 5, the surface density of the first active material layer is 50 g / m 2 The surface density of the second active material layer is 200 g / m 2 , the ratio of the thickness of the first active material layer to the thickness of the second active material layer is 2:8.
[0090] Comparative Example 6
[0091] The only difference between Comparative Example 6 and Example 1 is that in the composite positive electrode sheet described in Comparative Example 6, the active material layer only includes the first active material layer and no second active material layer, and the surface density of the first active material layer is consistent with that of Example 1.
[0092] Comparative Example 7
[0093] The only difference between Comparative Example 7 and Example 1 is that in the composite positive electrode sheet described in Comparative Example 7, the active material layer only includes the second active material layer, without the first active material layer, and the surface density of the second active material layer is consistent with that of Example 1.
[0094] Performance study of the composite positive electrode sheets described in Examples 1-2 and Comparative Examples 1-7 of the present application
[0095] The test method is as follows: 1. The mass ratio of the positive electrode sheet is: LFP (lithium iron phosphate composite material prepared in each embodiment or comparative example): PVDF: SP = 96.5:1.5:2. Wherein, PVDF is polyvinylidene fluoride and SP is conductive carbon black;
[0096] 2. The mass ratio of the negative electrode is: VTM-1: SP: SBR: CMC = 96.3:1:1.1:1.6. Among them, VTM-1 is graphite, SP is conductive carbon black, SBR is styrene-butadiene rubber, and CMC is carboxymethyl cellulose;
[0097] 3. Electrolyte model: Tianci TC-CN010;
[0098] 4. Choice of diaphragm: Enjie;
[0099] 5. Test method: average 2.5C-4C step charge, 1C constant current discharge, 3.65-2.50V.
[0100] The test results are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] It can be seen from Table 1 that: comparing Example 1, Example 2, Comparative Example 4, and Comparative Example 5, as the ratio of the thickness of the first active material layer to the thickness of the second active material layer increases, the rate performance of the battery cell gradually increases, and the energy density decreases. The increase in the proportion of large particles and the decrease in the proportion of small particles are conducive to the rapid infiltration of the electrolyte and the diffusion of lithium ions, thereby improving the rate performance. However, when the appropriate design range is exceeded, there is no significant increase in the energy density and rate benefit, and even a decrease in energy density and rate performance occurs. Comparing Example 1, Comparative Example 1, and Comparative Example 2, as the particle size of the first active material layer exceeds the appropriate range, being too large or too small will affect the rate performance and energy density of the battery cell. Although a too high particle size can improve the rate performance of the battery cell, it leads to a significant decrease in the energy of the battery cell, and the design requirements may not be met. A too low particle size will not improve the energy density of the battery cell, but will also lead to a decrease in the rate of the battery cell.
[0105] Comparing Example 1 and Comparative Example 3, the upper layer is small particles and the lower layer is large particles, and its rate performance is excellent. This is mainly because under the same conditions, in a thicker porous electrode, the transmission of lithium ions in and out of the active material is more dependent on the lithium ion diffusion capacity in the electrolyte than in a thinner porous electrode; Comparing Example 1, Comparative Example 6, and Comparative Example 7, the battery cell with a double active material layer has the advantage of meeting both energy density and rate performance relative to the battery cell with a single active material layer. Although the above embodiments have been shown and described, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Changes, modifications, replacements, and variations of the above embodiments made by ordinary technicians in this field are all within the scope of protection of the present invention.
Claims
1. A composite positive electrode sheet, characterized in that: It includes a current collector and active material layers symmetrically arranged on two sides of the current collector; The active material layer includes a first active material layer and a second active material layer; the current collector, the first active material layer and the second active material layer are sequentially overlapped; The first active material layer includes a first lithium iron phosphate, a first conductive agent and a first binder; The second active material layer includes a second lithium iron phosphate, a second conductive agent and a second binder; The secondary particles of the first lithium iron phosphate have a D50≤12 μm; and the secondary particles of the second lithium iron phosphate have a D50≤5 μm.
2. The composite positive electrode sheet according to claim 1, characterized in that: The D50 of the first lithium iron phosphate satisfies 6 μm≤D50≤12 μm, and the D50 of the second lithium iron phosphate satisfies 0.8 μm≤D50≤2.0 μm; And / or, the surface density of the first active material layer is 50-300 g / m 2 The surface density of the second active material layer is 50-300 g / m 2 ; And / or, the ratio of the thickness of the first active material layer to the thickness of the second active material layer is (3-5):(5-7).
3. The composite positive electrode sheet according to claim 1, characterized in that: The current collector comprises aluminum foil and / or carbon-coated aluminum foil; and / or, the first conductive agent and the second conductive agent each independently comprise conductive carbon black; And / or, the first binder and the second binder each independently include polyvinylidene fluoride.
4. The composite positive electrode sheet according to claim 1, characterized in that: The mass ratio of the first lithium iron phosphate to the first conductive agent is (96-97): (1-1.5); And / or, the mass ratio of the first lithium iron phosphate to the first binder is (96-98):
2.
5. The composite positive electrode sheet according to claim 1, characterized in that: The mass ratio of the second lithium iron phosphate to the second conductive agent is (96-98): (1-1.5); And / or, the mass ratio of the second lithium iron phosphate to the second binder is (96-98):
2.
6. The method for preparing the composite positive electrode sheet according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of the first layer of active material slurry: Mixing a first lithium iron phosphate, a first conductive agent, a first binder and a first solvent to obtain a first active material slurry; (2) Preparation of the second layer of active material slurry: Mixing a second lithium iron phosphate, a second conductive agent, a second binder, and a second solvent to obtain a second active material slurry; (3) The first active material slurry and the second active material slurry are simultaneously coated on the current collector and dried to obtain the composite positive electrode sheet.
7. The preparation method according to claim 6, characterized in that: The first solvent and the second solvent each independently include nitrogen methyl pyrrolidone.
8. The preparation method according to claim 6, characterized in that: The solid content of the first active material slurry is 60%-64%; and / or, the fineness of the first active material slurry is ≤20um; And / or, the viscosity of the first active material slurry is 5000-6000 mPa.s.
9. The preparation method according to claim 6, characterized in that: The solid content of the second active material slurry is 60%-64%; and / or, the fineness of the second active material slurry is ≤20um; And / or, the viscosity of the second active material slurry is 5000-6000 mPa.s.
10. The preparation method according to claim 6, characterized in that: The drying temperature is 80-110° C., and the drying time is 20-45 min.
Citation Information
Patent Citations
Lithium iron phosphate thick electrode and preparation method and application thereof
CN115394961A
Lithium iron phosphate positive plate as well as preparation method and application thereof
CN117219729A
Multilayer composite phosphate positive plate, preparation method thereof and battery
CN118431411A
Composite positive pole piece as well as preparation method and application thereof
CN118899404A